2016
DOI: 10.1007/s00281-016-0568-y
|View full text |Cite
|
Sign up to set email alerts
|

Basophil-derived IL-4 plays versatile roles in immunity

Abstract: Recent studies demonstrated that basophils play crucial and non-redundant roles in the immune system, in spite of the fact that they are the rarest granulocytes and represent less than 1 % of peripheral blood leukocytes. In response to various stimuli, basophils release effector molecules stored in their cytoplasmic granules, including chemical mediators and proteases, and also secrete cytokines and chemokines. In this review, we will focus on the physiological and pathological roles of basophil-derived IL-4. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 82 publications
0
31
0
1
Order By: Relevance
“…Although the initial source of IL‐4 still remains uncertain, basophils are proposed as a provider of initial IL‐4 that primarily induces Th2 cell differentiation . Indeed, basophils can readily secrete larger quantities of IL‐4 with lower threshold for activation than do Th2 cells on a per cell basis, in response to a variety of stimuli such as IgE plus allergens . Recent studies have identified versatile roles for basophil‐derived IL‐4 in immune responses, through its action on a variety of immune and non‐immune cells, including T cell, B cells, innate lymphoid cells, monocytes, macrophages, and fibroblasts …”
Section: Basophil‐derived Il‐4 Shows Anti‐inflammatory Activity Throumentioning
confidence: 99%
See 3 more Smart Citations
“…Although the initial source of IL‐4 still remains uncertain, basophils are proposed as a provider of initial IL‐4 that primarily induces Th2 cell differentiation . Indeed, basophils can readily secrete larger quantities of IL‐4 with lower threshold for activation than do Th2 cells on a per cell basis, in response to a variety of stimuli such as IgE plus allergens . Recent studies have identified versatile roles for basophil‐derived IL‐4 in immune responses, through its action on a variety of immune and non‐immune cells, including T cell, B cells, innate lymphoid cells, monocytes, macrophages, and fibroblasts …”
Section: Basophil‐derived Il‐4 Shows Anti‐inflammatory Activity Throumentioning
confidence: 99%
“…In turn, IL‐4 secreted by basophils conjugated with T cells efficiently promotes T cell differentiation toward Th2 cells. Other stimuli, including IgE plus allergens, IL‐33, and Toll‐like receptor ligands, may also induce IL‐4 production by basophils . In addition to IL‐4 production, basophils appear to have characteristics favorable for Th2 induction.…”
Section: Basophils Can Function As Th2‐oriented Antigen‐presenting Cementioning
confidence: 99%
See 2 more Smart Citations
“…Basophils rapidly secrete larger quantities of IL-4 than Th2 cells on a per cell basis in response to a variety of stimuli (15). IL-4 has an important role in promoting the differentiation of naive T cells to Th2 cells (16).…”
mentioning
confidence: 99%